Effort expectancy, task technology fit, and ERP adoption behavior: Moderating effect of trust in technology : evidence from SMEs of Pakistan - Waseem Subhani; Ahmad Shaharudin Abdul Latiff; Sazali Abdul Wahab (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Usually, adopting technology in the business boosts its performance, but SMEs are still reluctant to adopt modern technology such as ERP. This research has examined link among effort expectancy, task technology fit, and ERP adoption behavior in SMEs in Pakistan. Furthermore, this study examines the moderating effect of trust in technology on the said relationships. This study used a quantitative research technique. Google survey form method used to collect the data from employees of SMEs in Pakistan those having ERP systems. To measure and confirm the hypothesis, the study employed SmartPLS software. The findings show a significant linkage among effort expectancy, ERP adoption behavior, and task technology fit ERP adoption behavior. Besides the significance of direct relationships, the moderating effect of trust in technology is also significant in relation between effort expectancy, ERP adoption behavior, task technology fit and ERP adoption behavior, further strengthening the main hypothesis. This study's findings provide implications for organizations considering implementing an ERP system. By identifying the factors that influence ERP adoption behavior, organizations can develop strategies to increase the likelihood of successful implementation of ERP.
Keywords: 330; Effort expectancy; task technology fit; ERP adoption behaviour; trust intechnology; SMEs; Pakistan